Managing people : a competence approach to supervisory management - Collins, Michael.; Green, George.; Candy, Anita.; Cartwright, Roger. (Blackwell Business, 1998)
This book provides a practical and accessible means of acquiring the knowledge and understanding essential to better performance in the workplace, and to the acquisition of vocational qualifications.